2013
DOI: 10.5946/ce.2013.46.4.410
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mesenteric Artery Syndrome Diagnosed with Linear Endoscopic Ultrasound (with Video) in a Patient with Normal Body Mass Index

Abstract: Superior mesenteric artery (SMA) syndrome is an uncommon disease that results from SMA compression of the third portion of the duodenum. Patients with SMA syndrome present with upper gastrointestinal symptoms, such as nausea, vomiting, and abdominal pain. The diagnosis is usually made from an upper barium study or computed tomography. Typically, SMA syndrome is caused by a decreased aortomesenteric angle of 6° to 25°. An underweight body mass index (BMI) is a risk factor for development of SMA syndrome. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
2
1
1
Order By: Relevance
“…Similarly, Lee et al 29 observed SMAS occurrences in patients with normal BMIs, suggesting a possible link between a growth spurt and SMA configuration changes. Wee and colleagues and Wang and colleagues also contradicted our findings, indicating that low BMI is not always a prerequisite for decreased AMA and AMD in SMAS cases 30 , 31 .…”
Section: Discussioncontrasting
confidence: 65%
“…Similarly, Lee et al 29 observed SMAS occurrences in patients with normal BMIs, suggesting a possible link between a growth spurt and SMA configuration changes. Wee and colleagues and Wang and colleagues also contradicted our findings, indicating that low BMI is not always a prerequisite for decreased AMA and AMD in SMAS cases 30 , 31 .…”
Section: Discussioncontrasting
confidence: 65%
“…Any patient with sugestive symptoms for superior mesenteric artery syndrome should undergo imagistic investigation using upper gastrointestinal series, multisliced CT, CT angiography, magnetic resonance angiography, conventional angiography, ultrasonography and endoscopy (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…Un pacient pediatric cu simptome sugestive pentru sindromul de arteră mezenterică superioară necesită investigații endoscopice și radiologice amănunțite precum: computer tomografie, angio-CT, imagistică prin rezonanță magnetică, angiografie, ecografie și endoscopie digestivă superioară (5,14).…”
Section: Discuţiiunclassified